Gender and BCR‐ABL transcript type are correlated with molecular response to imatinib treatment in patients with chronic myeloid leukemia. (3rd July 2015) - Lin, Han‐Xin; Sjaarda, Jenny; Dyck, Jocob; Stringer, Randa; Hillis, Chris; Harvey, Maria; Carter, Ronald; Ainsworth, Peter; Leber, Brian; Pare, Guillaume; Sadikovic, Bekim
Abstract: Objectives: Achieving a major molecular response (MMR) is the goal of imatinib therapy for chronic myeloid leukemia. However, the association between gender, BCR‐ABL transcript type, and age with MMR is not well understood and often controversial. Methods: We retrospectively analyzed 166 patients who have been treated with imatinib for up to 10 yr. Results: Men had a lower MMR rate than women (63.3% vs. 81.6%, P = 0.006) and a shorter time to relapse (median 354 vs. 675 d, P = 0.049), while patients with b3a2 or with both b3a2 and b2a2 break point transcripts had higher MMR rate than those with b2a2 (81.8%, 77.1% vs. 60.7%, P = 0.023 for b3a2 vs. b2a2, P = 0.043 for both vs. b2a2). A striking difference was found between men with b2a2 and women with both b2a2 and b3a2 in terms of MMR rate (43.8% vs. 88.9%), MMR rate within 6 months (7.1% vs. 62.5%) and the time to MMR (median d 493 vs. 159, P = 0.036). Conclusions: Both gender and BCR‐ABL transcript, but not age, were significantly associated with the molecular response. Men with b2a2 represent a less favorable group in their response to imatinib treatment and may need alternative therapy regimen and closer monitoring.